Komunikasi Persuasi dalam Strategi Pemasaran Jastip Barang Impor - Irma Septuriany Dewanti; Eli Jamilah Miharja (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Jastip or the abbreviation of Jasa titip is a convenience in transactions to buy goods where someone acts as an intermediary for the purchase of goods from within the country or abroad that cannot be accessed directly by the buyer of the goods. The party providing the titip service will make the purchase and send the goods according to the customer's request, by obtaining a commission or additional fee for the service. The phenomenon in this study is in the form of communication phenomenology, because Jastip imported goods have become an integral part of the global trade ecosystem where individuals or companies take on the role of intermediaries between local consumers and imported goods from abroad. Through a qualitative approach and case studies, this study aims to determine how persuasive communication is used by Jastip service providers to influence consumer perceptions and behavior.